2019
DOI: 10.1111/ijpo.12606
|View full text |Cite
|
Sign up to set email alerts
|

Fast food, beverage, and snack brands on social media in the United States: An examination of marketing techniques utilized in 2000 brand posts

Abstract: Summary Background Exposure to food advertisements is associated with poor diet among youth, and food and beverage companies are increasingly advertising on social media sites that are popular among youth. Objective To identify the prevalence of social media advertising among fast food, beverage, and snack companies and examine advertising techniques they use on Instagram, Facebook, Twitter, Tumblr, and Vine. Methods We quantified the increase in the creation of social media accounts from 2007 to 2016 among 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
111
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(116 citation statements)
references
References 27 publications
1
111
0
4
Order By: Relevance
“…Bragg 76 concluded that accounts for food, beverage, and snack brands on five social media platforms (i.e., Instagram, Facebook, Twitter, Tumblr, and Vine) increased 567% between 2007 and 2016. Two thirds (67.9%) of promoted foods were unhealthy, and 61.2% of beverages were sugary beverages 76 . Nineteen percent of all identified posts featured a celebrity or cross‐promotional theme (e.g., Olympics) 76 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bragg 76 concluded that accounts for food, beverage, and snack brands on five social media platforms (i.e., Instagram, Facebook, Twitter, Tumblr, and Vine) increased 567% between 2007 and 2016. Two thirds (67.9%) of promoted foods were unhealthy, and 61.2% of beverages were sugary beverages 76 . Nineteen percent of all identified posts featured a celebrity or cross‐promotional theme (e.g., Olympics) 76 .…”
Section: Resultsmentioning
confidence: 99%
“…Two thirds (67.9%) of promoted foods were unhealthy, and 61.2% of beverages were sugary beverages 76 . Nineteen percent of all identified posts featured a celebrity or cross‐promotional theme (e.g., Olympics) 76 . Additionally, Fleming‐Milici 77 examined food and beverage marketing on tablet, smartphone, or other digital and mobile devices found that 70% of adolescents engaged with food and beverage brands on social media, and 50% engaged with unhealthy food and beverage products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings build upon those studies by demonstrating that 6.2 million adolescents are following food and beverage ads on Instagram and Twitter. Adolescents' willingness to "opt in" for additional advertising exposure is concerning given that these brands post thousands of ads on social media annually [34]. The Federal Trade Commission should require disclosures (e.g., "This is advertising") on posts made by food and beverage companies who manage these free social media accounts.…”
Section: Discussionmentioning
confidence: 99%
“…37 On the other hand, studies of the exposure of advertising directed to children and adolescents in social network, reported that 61% of the posts correspond to SSBs. 38 Some studies found that up to 14% of product packages aimed at children use technology packaging (suckers, unusual shapes or straws). 32,35 We reported that 53.1% of beverages with child-directed strategies use this strategy, but this difference can be explained by the type of products analyzed; it is more common for beverages to T A B L E 4 Proportion of advertising strategies to children stratified by types of beverage in beverages with child-directed strategies (n = 405) called this strategy "technology of packaging", which is more frequent in products aimed at children.…”
Section: Discussionmentioning
confidence: 99%